Perceptions toward antiretroviral therapy and delayed ART initiation among people living with HIV in Changsha, China: mediating effects of treatment willingness - Zhou, Yaqin; Li, Yixuan; Xiao, Xueling; Qian, Han-Zhu; Wang, Honghong (Frontiers in Public Health, 2023)
Delayed antiretroviral therapy (ART) initiation is associated with poor HIV outcomes and a higher likelihood of HIV transmission. This cross-sectional study assessed the proportion of delayed ART initiation which was defined as initiating ART after 30 days of HIV diagnosis, and evaluated the pathways influencing ART initiation among adult PLWH in Changsha, China who were diagnosed between 2014 and 2022. Of 518 participants, 37.8% delayed in initiating ART. Based on the theory of reasoned action (TRA), delayed initiation was indirectly associated with perceptions toward ART through the mediating pathway of patients’ treatment willingness, with treatment willingness significantly being the full mediator. The findings may guide the development of interventions to improve timely uptake of ART in people who are newly diagnosed with HIV.